Malaysian Technical University Students Mental Health Profile - F. Lee, M; S. Lai, C (International Journal of Engineering and Technology, 2018)
This paper discuss about the Malaysian Technical University (MTU) studentsâ€™ mental health issue. This article aims to develop a profile of MTU students on mental health issue from the aspect of gender, year of study and field of study. A stratified random sampling technique was applied to select about 450 students as the sample in this study. The DASS-21 inventory was adopted as instrument for this study. The obtained data were analysed by using frequencies, percentage, mean, standard deviation, Independent T-test, one-way ANOVA and LSD post-hoc test. The findings showed that there is no significant difference in mental health issue from the gender aspect, but there is a significant difference from the aspect of year of study and field of study. As a conclusion, intervention program needs to be conducted to solve the mental health issue in order to help the students to achieve a better academic performance.Â